2009
DOI: 10.4038/cmj.v54i2.793
|View full text |Cite
|
Sign up to set email alerts
|

Do Sri Lankan meals help decrease blood glucose response?

Abstract: Objective The prevalence of diabetes mellitus (DM) has rapidly increased in Asian countries including Sri Lanka during the past decade. Scientific data on postprandial glycaemic influence of common meals is essential when formulating diets. Objectives of this study were to analyse glycaemic indices (GI) of five common meals and effects of macronutrients, sources of carbohydrates, and physicochemical properties of starch on observed GI values. Design The meals analysed were; 1-red rice (AT 353) meal, 2-red rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
(13 reference statements)
3
19
0
Order By: Relevance
“…The differences in starch structure in different rice varieties may contribute to the differences in GI. Hettiaratchi et al, had shown that accompanying foods could reduce the the GI of a rice meal [4]. In this study rice was served with coconut sambol (25g).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The differences in starch structure in different rice varieties may contribute to the differences in GI. Hettiaratchi et al, had shown that accompanying foods could reduce the the GI of a rice meal [4]. In this study rice was served with coconut sambol (25g).…”
Section: Resultsmentioning
confidence: 94%
“…Patients with metabolic disorders such as diabetes or hyperlipidaemia are recommended low-GI diets which give rise to a low and slow glycaemic response thus avoiding sudden fluctuations in the glycaemic response [2,3]. Despite being the staple food and the major contributor to carbohydrate intake, little data is available on the GI of local rice varieties [4][5][6][7]. Recently GI data on two imported basmati varieties available in the Sri Lankan market was reported [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High glycaemic index (GI) meals like bread [15], short eats, string hoppers [16], pittu (a steam cooked food made with rice flour and coconut), and so forth [17] are consumed by 17.8% for ≥5 days/week as breakfast while 8.9% consumed boiled legumes (low GI [17]) for breakfast. Consumption of rice meal as breakfast for all 7 days of the week was by 45.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of high GI foods (white bread [15] and string hoppers [16], etc.) for dinner was by 13.3% (for 3 or more than 3 days/week) while only 4.4% relies on light diets (soup/soup with biscuits/biscuits with milk/small portion of a main meal/fresh fruits or vegetables, etc.)…”
Section: Resultsmentioning
confidence: 99%